2008
DOI: 10.1038/nrm2321
|View full text |Cite
|
Sign up to set email alerts
|

Argonaute proteins: key players in RNA silencing

Abstract: During the past decade, small non-coding RNAs have rapidly emerged as important contributors to gene regulation. To carry out their biological functions, these small RNAs require a unique class of proteins called Argonautes. The discovery and our comprehension of this highly conserved protein family is closely linked to the study of RNA-based gene silencing mechanisms. With their functional domains, Argonaute proteins can bind small non-coding RNAs and control protein synthesis, affect messenger RNA stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
912
1
16

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,176 publications
(945 citation statements)
references
References 136 publications
16
912
1
16
Order By: Relevance
“…Proteins with Piwi domains have been described as components of ribonucleoprotein complexes that act in the microRNA/ RNA interference pathway of gene silencing (Fetzer et al, 2002, Lingel et al, 2005. Recently, it was shown that the Piwi gene family are associated with a new class of small RNAs socalled 'piwi-interacting RNAs' (piRNAs) in mammalian spermatogenesis (Hall et al, 2005, Houwing et al, 2007, Hutvagner et al, 2008, Peters et al, 2007, which is one of gene expressing regulatory small non-coding RNAs (ncRNAs). Small ncRNAs are naturally conserved regulators of gene expression described in almost all eukaryotic species including humans (Elbashir et al, 2001, Meister et al, 2004, Sana et al, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins with Piwi domains have been described as components of ribonucleoprotein complexes that act in the microRNA/ RNA interference pathway of gene silencing (Fetzer et al, 2002, Lingel et al, 2005. Recently, it was shown that the Piwi gene family are associated with a new class of small RNAs socalled 'piwi-interacting RNAs' (piRNAs) in mammalian spermatogenesis (Hall et al, 2005, Houwing et al, 2007, Hutvagner et al, 2008, Peters et al, 2007, which is one of gene expressing regulatory small non-coding RNAs (ncRNAs). Small ncRNAs are naturally conserved regulators of gene expression described in almost all eukaryotic species including humans (Elbashir et al, 2001, Meister et al, 2004, Sana et al, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that CSCs which are self-renewing and differentiate into heterogeneous tumor cells, are responsible for the drug resistance and tumor relapse (Yu et al, 1995). Hiwi gene, a human homologue of the Piwi family which plays an important role in stem cell self-renewal (Cox et al, 1998;Hutvagner et al, 2008), had been shown to be highly expressed in a variety of human cancers (Liu et al, 2006;Grochola et al, 2008). Moreover, recent data suggested that Hiwi gene was required to maintain the stemness of hematopoietic stem cells (Sharma et al, 2001).…”
Section: Hiwi Knockdown Inhibits the Growth Of Lung Cancer In Nude Micementioning
confidence: 99%
“…RNA silencing is a small regulatory RNA-mediated biological process conserved in plants and animals (Tomari & Zamore, 2005;Patel et al, 2006;Hutvagner & Simard, 2008). In plants, RNA silencing is believed to be an ancient immune response triggered against viral double-stranded RNAs (dsRNAs; Ding & Voinnet, 2007).…”
Section: Introductionmentioning
confidence: 99%